1993
DOI: 10.1111/j.1399-3054.1993.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinins in photoperiodic induction of flowering in Chenopodium species

Abstract: Changes in cytokinin (zeatin – Z, zeatin riboside – ZR, isopentenyladenine – iP, isopentenyladenosine – iPA) levels were determined under light regimes inductive and non‐inductive for flowering in leaves, stems, roots and apical parts of short‐day Chenopodium rubrum and long‐day Chenopodium murale. In leaves. stems and roots of both plant species the level of cytokinins (in C. rubrum of Z and ZR, in C. murale of Z. ZR, iP and iPA) decreased by about 50% during the dark period and increased again during the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 11 publications
(6 reference statements)
4
29
0
Order By: Relevance
“…In tobacco leaves the level of all CKs determined was about three times higher at the end of the dark period than at the end of the light period, which shows that the changes observed in C. rubrum (Machácková et al, 1993) are not general and may be correlated with the photoperiodic type of the plant. The relative abundance of individual CKs remained almost unchanged (Tables III and IV).…”
Section: Content Of Cks In Chloroplasts From Tobacco and Wheat Leavesmentioning
confidence: 83%
See 1 more Smart Citation
“…In tobacco leaves the level of all CKs determined was about three times higher at the end of the dark period than at the end of the light period, which shows that the changes observed in C. rubrum (Machácková et al, 1993) are not general and may be correlated with the photoperiodic type of the plant. The relative abundance of individual CKs remained almost unchanged (Tables III and IV).…”
Section: Content Of Cks In Chloroplasts From Tobacco and Wheat Leavesmentioning
confidence: 83%
“…We do know from our recent work on the role of CKs in the flowering of Chenopodium rubrum (Machácková et al, 1993) that the levels of free CKs (bases and ribosides) in leaves decrease during the dark period, probably due to changes in the conversion to ribotides. As the first step in unraveling this complex system, we analyzed the CK levels in wheat leaves and in the leaves and chloroplasts of tobacco taken for chloroplast preparation at the end of a 12-h period of light or dark.…”
Section: Content Of Cks In Chloroplasts From Tobacco Upper and Lower mentioning
confidence: 99%
“…Earlier work in Chenopodium showed that after the photoperiodic induction of flowering, cytokinin content decreased (Machackova et al, 1993). Exogenous cytokinin application after the inductive photoperiod also inhibited flowering in this species (I.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the 24-and 26-kD proteins Davelaar, 1981;Taylor et al, 1990). Cytokinins have frequently been implicated as an essential component of the eventual floral response (Bernier et al, 1977;Lejeune et al, 1988;Machackova et al, 1993). Although zeatin and zeatin riboside levels do not increase dramatically in ice plant roots or leaves during the salt-stress period (Thomas et al, 1992b), we do not exclude temporally and spatially localiied changes in growth regulator concentration during salt stress or changes in titer of distinct cytokinins that have been shown to specifically contribute to flowering responses (van der Krieken et al, 1991).…”
Section: Discussionmentioning
confidence: 99%